Judo and Kindene: the relationship between the sportification of Japenese combat sport and Brazilian indigenous wrestling - Tavares, Antonio Carlos [UNESP]; Costa, Carlos Eduardo; Pimenta, Thiago de Fonseca Farias (My University, 2024)
Background. Combat sports are a social reconfiguration of martial arts and due to their origins and peculiar historical processes, are endowed with a set of specific and complex sociocultural practices and anthropological manifestations. Norbert Elias and Eric Dunning used the word “sportification” to define the phenomenon of transforming pastimes (games) into sports and exporting them on an almost global scale. According to the authors, such a phenomenon occurs due to the “process of civilization.” Problem and Aim. To draw the parallels between the sportification of Judo and Kindene and to present information related to the social, historical, motor, and regulatory aspects. Methods. The study has a descriptive profile and a qualitative approach. It presents information about Kindene and Judo in an organized way, through documental analysis and a brief literature review, of a case study. Results. Similar to what was proposed by Elias and Dunning with modern sports in the European context, Judo and Kindene were also used as pacification strategies by groups with greater power and possibilities. By the Order of the Emperor himself in Japan or of the chiefs in the Upper Xingu. Conclusions. Both modalities contributed to the pacification of relationships through a civilization process, which also occurred in the modalities themselves. In the Japanese case, we observe this civilization process in the transformation of Bujutsu into Budo until the formation of judo as a combat sport. In the case of Kindene, we see the redefinition of a system of conflicts of war to a system of ritual combat geared towards performances and the consolidation of interethnic relationships.
Keywords: combat sports; cultural manifestation; Judo; Kindene; sportification